2011
DOI: 10.1523/jneurosci.0618-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

 -Syn Suppression Reverses Synaptic and Memory Defects in a Mouse Model of Dementia with Lewy Bodies

Abstract: Abnormally accumulated α-syn is a pathological hallmark of Lewy body related disorders such as Parkinson’s disease (PD) and Dementia with Lewy body disease (DLB). However, it is not well understood whether and how abnormal accumulation of α-syn leads to cognitive impairment or dementia in PD and DLB. Furthermore, it is not known whether targeted removal of α-syn pathology can reverse cognitive decline. Here we find that the distribution of α-syn pathology in an inducible α-syn transgenic mouse model recapitula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
117
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(132 citation statements)
references
References 50 publications
15
117
0
Order By: Relevance
“…As previously discussed, even though widespread overexpression of alpha-synuclein is preferable to expression restricted to catecholaminergic neurons to model PD, it is important to ensure that alpha-synuclein over-expression does occur in the nigrostriatal dopaminergic neurons, which are severely affected in the disease. In contrast, models with primary accumulation of alpha-synuclein in the forebrain more closely model dementia with Lewy bodies, in which severe cognitive deficits appear earlier than extrapyramidal motor deficits [23,27]. Both mRNA measurements in laser-captured nigrostriatal dopaminergic neurons (Fig.…”
Section: Lifespan and General Health In Thy1-asyn Micementioning
confidence: 98%
“…As previously discussed, even though widespread overexpression of alpha-synuclein is preferable to expression restricted to catecholaminergic neurons to model PD, it is important to ensure that alpha-synuclein over-expression does occur in the nigrostriatal dopaminergic neurons, which are severely affected in the disease. In contrast, models with primary accumulation of alpha-synuclein in the forebrain more closely model dementia with Lewy bodies, in which severe cognitive deficits appear earlier than extrapyramidal motor deficits [23,27]. Both mRNA measurements in laser-captured nigrostriatal dopaminergic neurons (Fig.…”
Section: Lifespan and General Health In Thy1-asyn Micementioning
confidence: 98%
“…Detailed structural analysis revealed that Ser87 is inaccessible to casein kinase when α-synuclein is fibrillar, although Ser129 may be phosphorylated after fibril formation has occurred, raising more uncertainty about the cause-and-effect relationship between α-synuclein phosphorylation, aggregation, and neurotoxicity [60]. Moreover, A53T-α-synuclein expressing mice show Ser129 phosphorylated α-synuclein that presents in heterogeneous discrete but overlapping patterns, suggesting that phosphorylation is not a prerequisite for α-synuclein aggregation and may be a marker of advanced pathology [202]. Perhaps phosphorylated α-synuclein is cleared less effectively, consistent with a secondary effect of phosphorylation [189].…”
Section: Phosphorylationmentioning
confidence: 99%
“…Bypassing these post-natal developmental defects by suppression of the transgene until post-natal day 21 led to abnormal accumulation of α-synuclein in the hippocampus, which correlated with memory impairment and structural synaptic deficits. Interestingly, when α-synuclein expression was suppressed, partial pre-clearing of existing α-synuclein aggregates and improvement in memory function were observed [169]. While α-synuclein overexpression driven by the CaMKIIα-tTA promoter reproduced only a few features of PD, the use of the GFAP-tTA promoter led to astrocytic expression of A53T α-synuclein and resulted in a 60% loss of TH-positive neurons in the SN [156].…”
Section: Genetic Mouse Models: Lessons Learned From α-Synuclein-overementioning
confidence: 99%